Interdependence of parasitic losses in photonic crystal surface emitting lasers - Jingzhao Liu; Xingyu Zhao; Zijun Bian; Paul Harvey; Scott Watson; Stephen J. Sweeney; Richard Hogg (AIP Advances)
It is common practice to use an un-pumped, PC containing region of a PCSEL to reduce in-plane optical power loss. We simulate the effect of self-absorption in this un-pumped region on parasitic losses. It is found that the in-plane loss may be zeroed for a suitably thick un-pumped PC region width. However, in such devices, the internal loss no longer has a unique value, and the dependence of the minimum total parasitic loss on a range of parameters is discussed.